Case report of the rare Peters' anomaly complicated with Axenfeld-Rieger syndrome: A case report and brief review of the literature. Issue 2 (14th January 2022) - Meng, Yong; Lu, Guohua; Xie, Yang; Sun, Xincheng; Huang, Liqin
Abstract: Introduction: Peters' anomaly (PA) and Axenfeld-Rieger syndrome (ARS) are typical classifications of anterior segment dysgenesis (ASD) and ascribed to congenital eye diseases that encompass developmental defects in anterior segment structures. The aim of this study is to discuss the unusual association between PA and ARS and to determine the results of penetrating keratoplasty combined with extracapsular cataract extraction and anterior vitrectomy for this unusual ophthalmic phenotype. Patient concerns: A 72-year-old female was referred to Changzhou No. 2 People's Hospital for a progressive decrease in visual acuity in both eyes in the past few decades. Diagnoses: The patient was diagnosed with PA with cone-shaped polar cataracts in the left eye based on a series of ophthalmic examinations. ARS with retinal detachment was diagnosed in the right eye 2 years prior. Interventions: Penetrating keratoplasty combined with extracapsular cataract extraction and anterior vitrectomy were performed to manage PA with cataracts in the left eye. Outcomes: Her best corrected visual acuity did not improve significantly after the operation. Patients with ARS and PA should be treated cautiously because of fundus lesions. Conclusion: This study revealed that cases with PA accompanied by iridocorneal adhesions, or other ocular anomalies, need to be treated cautiously for a very low success rate. It is of reference value for the evaluation of treatment prognosis for this joint occurrence of ophthalmic phenotypes.